Ethical inclusion in community research: a comment on ‘Consent, assent and randomised evaluations’ by Michael Sanders et al - Marc Atkins (Evidence & Policy, 2023)
This commentary responds to points raised by Sanders et al in ‘Consent, assent and randomised evaluations’ ( Evidence & Policy , 19(4): 603–605, 10.1332/174426421X16842419724551).